A ZnO nanowire resistive switch - Ramanujam Prabhakar, Rajiv (2013)
An individual ZnO nanowire resistive switch is evaluated with Pt/ZnO nanowire/Pt topology. A detailed DC I-V curve analysis is performed to bring both the conduction mechanism and the device characteristics to light. The device is further studied at various vacuum pressures to ascertain the presence of polar charges in ZnO nanowires as the phenomenon leading to the formation of the switch. The disappearance of the resistive switching is also analyzed with two kinds of fabrication approaches Focused Ion/Electron Beam involved in the making the device and a summary of both length and fabrication dependences of resistive switching in the ZnO nanowire is presented.